Attuning to laboratory animals and telling stories: Learning animal geography research skills from animal technologists - Greenhough, B; Roe, E (Sage Publishing, 2018)
Posthumanism has challenged the social sciences and humanities to rethink anthopocentricism within the cultures and societies they study and to take account of more-than-human agencies and perspectives. This poses key methodological challenges, including a tendency for animal geographies to focus very much on the human side of human–animal relations and to fail to acknowledge animals as embodied, lively, articulate political subjects. In this paper, we draw on recent ethnographic work, observing and participating in the care of research animals and interviewing the animal technologists, to contribute to the understandings of life within the animal house. In so doing, the paper makes three key arguments. Firstly, that studying how animal technologists perform everyday care and make sense of their relationships with animals offers useful insights into the specific skills, expertise and relationships required in order to study human–animal relations. Secondly, that animal technologists are keenly aware of the contested moralities which emerge in animal research environments and can offer an important position from which to understand this. Thirdly, that storytelling (exemplified by the stories told by animal technologists) is a useful resource for animal geographers to engage with complexity in human–animal relations.